2017
DOI: 10.1038/s41598-017-16552-6
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gases emissions in rivers of the Tibetan Plateau

Abstract: Greenhouse gases (GHGs) emissions from streams are important to regional biogeochemical budgets. This study is one of the first to incorporate stream GHGs (CO2, CH4 and N2O) concentrations and emissions in rivers of the Tibetan Plateau. With one-time sampling from 32 sites in rivers of the plateau, we found that most of the rivers were supersaturated with CO2, CH4 and N2O during the study period. Medians of partial pressures of CO2 (pCO2), pCH4 and pN2O were presented 864 μatm, 6.3 μatm, and 0.25 μatm respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 65 publications
5
27
1
Order By: Relevance
“…There was no data insofar from the origin of the Mekong River. But the research on three rivers on the Tibetan Plateau shows a median pCO2 of 864 µatm, which was comparable to the values in the GGQ (Qu et al, 2017).…”
Section: Spatial and Seasonal Variation Of Pco2 10supporting
confidence: 67%
“…There was no data insofar from the origin of the Mekong River. But the research on three rivers on the Tibetan Plateau shows a median pCO2 of 864 µatm, which was comparable to the values in the GGQ (Qu et al, 2017).…”
Section: Spatial and Seasonal Variation Of Pco2 10supporting
confidence: 67%
“…Twenty milliliters of N 2 was added to the syringe. The syringe was then shaken (underwater to maintain constant temperature) for 2 min to equilibrate the headspace with the water sample (Kling et al, ; Qu, Aho, et al, ). A 15 mL of headspace sample was then injected into a vaccumed airtight Exetainer vial (Labco Exetainer®, UK).…”
Section: Methodsmentioning
confidence: 99%
“…In a permafrost covered region, the riverine pCO 2 exhibited a statistically significant and negative linear relationship with pH (Table 1), which is likely because the dissolved CO 2 itself acts as an acid in water [42]. In poorly buffered systems like the YRSR, pH can be a strong indicator of the dissolved CO 2 [14,19]. The DOC concentrations in the permafrost rivers (mean: 5.0 ± 2.4 mg L −1 ) were relatively higher than in the glacier rivers (mean: 3.6 ± 1.1 mg L −1 ) and the grassland rivers (4.6 ± 2.3 mg L −1 ), but were comparable to the peatland rivers of 5.1 ± 3.7 mg L −1 .…”
Section: Impact Of Land Cover Types On Riverine Pco 2 and Co 2 Outgasmentioning
confidence: 99%
“…Additionally, with increasing temperature, the carbon stored in permafrost layers and glaciers are likely to be mineralized and emitted into the atmosphere from river networks [16,18]. Recent studies on the Yellow River source Region (YRSR) showed inconsistent findings from a carbon source [19] to a carbon sink [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation